Wycena i raportowanie kapitału intelektualnego - case study na przykładzie firmy szkoleniowo-doradczej (T&C) - Osbert-Pociecha, Grażyna; Pociecha, Wojciech (Valuation and Reporting Intellectual Capital (Ic) in Training & Consulting Firm (Case Study), 2006)
This article emphasizes that IC is both a very important condition of development strategy of firm and the element of its competition advantage. The review of literature shows that IC could be defined and measured in many ways. For the meantime in our practice still dominate standards which don't take into consideration the intangible assets of firm. It was exemplified of firm which belongs to services sector of training and consulting. First, the firm's IC was evaluated and it turned out that its value is higher than the value of assets presented in financial report. So in this situation the authors suggested instrument of reporting some elements of IC. It should be a supplement of traditional reporting system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 90-106